التنظيم الذاتي وعلاقته بالمخدرات الرقمية لدى طالبات المرحلة المتوسطة - حمادي، لقاء شريف عبد (جامعة بابل - كلية التربية للعلوم الإنسانية, 2023)
تعد المدرسة احد مكونات المجتمع ومن اهم المؤسسات الفاعلة به وتوصف كمنظومة ضابطة تتكون من مجموعة من العناصر تربطهم علاقة تفاعلية يعمل كل فرد كنظام فرعي ضابط لإشباع حاجاته الخاصة ليحافظ على دوره في ضبط النظام المدرسي بشكل عام لكي يشبع حاجاته العامة ويحقق أهدافه الخاصة، وتقوم على آلية القدوة الحسنة مع استخدام الحوار والمناقشة الهادفة والثواب والتحفيز بدل العقاب والتنظيم الذاتي الإيجابي لخلق فرد متزن انفعاليا محافظ على حقوقه وواجباته، وتكمن مشكلة البحث الحالي في الإجابة على السؤال الاتي: ما هي العلاقة بين التنظيم الذاتي والمخدرات الرقمي لدى طلبة المرحلة المتوسطة؟ و يهدف البحث إلى التعرف على التنظيم الذاتي لدى طالبات المرحلة المتوسطة، والمخدرات الرقمية لدى طالبات المرحلة المتوسطة، والعلاقة بين التنظيم الذاتي والمخدرات الرقمية لدى طالبات المرحلة المتوسطة، واتبعت الباحثة منهج البحث الوصفي (علاقة ارتباطية) وقامت ببناء أدوات البحث بما يتناسب مع نوع العينة إذ طبقت المقاييس على عينة تم اختيارها بالطريقة العشوائية البسيطة، وأسفرت نتائج البحث إلى: إن طالبات المرحلة المتوسطة يتمتعن بالتنظيم الذاتي، وان طالبات المرحلة المتوسطة يتعاطين المخدرات الرقمية، وإن للتنظيم الذاتي علاقة طردية مع المخدرات الرقمية لدى طالبات المرحلة المتوسطة، وفي ضوء نتائج الدراسة وضعت الباحثة مجموعة من التوصيات والمقترحات. The school is one of the components of the society and one of the most important institutions active in it, and it is described as a controlling system consisting of a group of elements that have an interactive relationship. And it is based on the mechanism of good example with the use of dialogue and purposeful discussion and reward and motivation instead of punishment and positive self-regulation to create an emotionally balanced individual who maintains his rights and duties, and the problem of the current research lies in answering the following question: What is the relationship between self-regulation And digital drugs among middle school students? The research aims to identify self-regulation among middle school students, digital drugs among middle school students, and the relationship between self-regulation and digital drugs among middle school students. The researcher followed the descriptive research method (correlation ship) and built research tools including: It is commensurate with the type of the sample, as the measures were applied to a sample that was chosen by the simple random method, And the results of the research resulted in: middle school students enjoy self-regulation, middle school students use digital drugs, and self-regulation has a positive relationship with digital drugs among middle school students, and in light of the results of the study, the researcher developed a set of recommendations and proposals.
Keywords: التنظيم الذاتي -- الإدمان الرقمي -- الإرشاد التربوي -- طلبة المرحلة المتوسطة